High-Gain-Integrated Switched Capacitor Indirect Matrix Converter - Raghuram M.; Chauhan A.K.; Singh S.K. (My University, 2025)
An ultrasparse matrix converter (USMC) is a derived form of an indirect matrix converter having a less number of switches. Even though it has unidirectional power flow capability, it is a quite appropriate candidate for specific applications, such as wind-energy systems, electrohydrostatic actuators, variable speed drives, and so on. However, the gain of the converter is still limited irrespective of various topological and control strategy modifications. Unlike the previous propositions, this paper is primarily focused on the integration of a switched capacitor boost network within the USMC to enhance gain, by preserving the advantages of the USMC. For controlling the proposed converter, a modified space vector modulation technique is also presented in this paper. In order to explore the potential of the proposed converter, analytical expressions are derived. The theoretical findings are further verified using simulation and experimental results. © 2013 IEEE.